Carbon Dioxide Emissions from Exhumed Petrocalcic Horizons - Serna-Pérez, A; Monger, H.C; Herrick, J.E; Murray, L (Soil Science Society of America journal, 2006)
The second largest pool of terrestrial carbon is soil CaCO₃. In addition to being an important sink of atmospheric CO₂, soil carbonate is potentially an important source of atmospheric CO₂. The cemented form of soil carbonate-the petrocalcic horizon-develops in geomorphically stable soil in arid, semiarid, and some subhumid climates. In many of these dryland areas, such as the Chihuahuan Desert of North America, erosion has stripped away overlying soil and exhumed the petrocalcic horizon, thereby exposing it to a weathering zone above the calcification zone where it normally forms. This research tested the hypothesis that soil type 1 (eroded Aridisols with exhumed petrocalcic horizons) will emit more CO₂ than soil type 2 (noneroded Aridisols with petrocalcic horizons) or soil type 3 (Entisols formed in sandy, noncalcareous sediments). We tested this hypothesis by comparing the amount of CO₂ and the delta 13C of CO₂ released from the three soil types. Using a randomized complete block design, CO₂ emissions were measured using NaOH and soda lime traps from June 2002 to October 2003. Neither the NaOH traps nor soda lime traps detected any statistical difference in cumulative CO₂ emissions from the three soil types at the = 0.05 level. Moreover, the isotopic analysis of CO₂ did not match the isotopic values of pedogenic carbonate, nor were there any statistical differences (α= 0.05) in delta 13C of CO₂ among the three soil types. We conclude, therefore, that exhumed petrocalcic horizons are not actively emitting CO₂ at a rate significantly greater than adjacent soils, and thus carbon stored in petrocalcic horizons can be considered a recalcitrant reservoir within the decadal timeframe pertinent to carbon sequestration policies.